Quantification of the enhancement of PM2.5 concentration by the downward transport of ozone from the stratosphere. (September 2020) - Chen, Lei; Xing, Jia; Mathur, Rohit; Liu, Shuchang; Wang, Shuxiao; Hao, Jiming
Abstract: The downward transport of ozone (O3 ) stemming from the stratosphere-to-troposphere exchange (STE) can be a significant contributor to background O3 . Such enhancement of background O3 may also influence ground-level PM2.5, particularly in polluted regions which have abundant precursor emissions. In this study, we quantified the STE impact on tropospheric O3 and its subsequent influence on surface PM2.5 across the northern hemisphere. The sensitivity analyses was conducted by using a comprehensive hemispheric atmospheric modeling system. Results suggest the surface PM2.5 concentration can be considerably enhanced by the STE in polluted regions including East China, East US, and Europe, mostly in winter and spring. In winter, the PM2.5 concentrations in East China, East US, and Europe are estimated to be enhanced by 1.3%, 3.5% and 5.5% due to the STE. The STE-enhanced PM2.5 concentrations are typically higher on high pollution days suggesting likely increasing contributions in regions with the growing pollution levels. During the heavy polluted days, the PM2.5 concentrations in East China can be enhanced by 2.289 μg/m 3 in winter and 2.034 μg/m 3 in spring due to the STE. The STE-enhanced PM2.5 also exhibits strong diurnal variations following a pattern similar to the total PM2.5 concentration, with high increasing ratio in the morning and low at afternoon, suggesting that the enhancement is most pronounced during peak pollution events. The STE-enhanced PM2.5 is exclusively contributed by the increase of nitrate, ammonium, and secondary organic aerosol which in-turn are strongly influenced by the atmospheric oxidation capacity. Highlights: STE-driven O3 downward transport can lead to non-trivial enhancement of surface PM2.5 STE-enhanced PM2.5 is most pronounced in polluted regions. STE enhances peak PM2.5 thereby further exacerbating high pollution levels. STE-enhanced PM2.5 is exclusively caused by an increase of secondary aerosols. STE enhancement on SOA becomes more important during heavier polluted period.